Removal Total chromium in water using activated coal microwave radiation - de la Torre Ostos, Juan (2017)
Removal of chromium was studied to validate the use of activated carbon by microwave radiation. This activation technique was previously used in the oxidation of carbon nanotubes and charcoal. It was tried to apply this technique in a coal of mineral origin, coming from the coal mines of the Santa - Ancash river basin and to improve the properties of removal of this material, with which in the long term and to greater investigation would be possible to give a use Apart from the one that is currently destined. The experimental activation tests were successful, this reflected in the removal kinetics of chromium; the removal capacity values determined in said kinetics are between 34% for unconverted coal and 41% for activated charcoal, which indicates that the removal capacity is highly dependent on the activation of the material.